Spanning Tests for Assets with Option-Like Payoffs: The Case of Hedge Funds - Karehnke, Paul; de Roon, Frans (Management Science, 2020)
We draw on the skewness literature to propose regression-based performance evaluation tests designed for investments with option-like returns. These tests deliver conclusions valid for all risk-averse mean-variance-skewness investors and can better account for nonlinearities in returns than option-based factor models. Applied to mutual and hedge funds, our tests usually suggest selecting different funds than standard tests and find that a significant fraction (11%) of hedge funds adds value to investors, whereas this is an insignificant 4% for mutual funds. We also analyze the economic significance of these option-like returns and their out-of-sample persistence. This paper was accepted by Tyler Shumway, finance.